From Childhood Migraine Headache to Pheochromocytoma - Y. M. Hazimeh; M. Luidens; M. E. Ehlers; V. Sharma (Case Reports in Endocrinology)
Pheochromocytoma may have multiple clinical manifestations including paroxysmal hypertension, tachycardia, sweating, nausea, and headache (Phillips et al., 2002). Migraine has some of the manifestations seen with pheochromocytoma. We describe a patient who had a history of migraine headaches since childhood and was found to have pheochromocytoma. Resection of her tumor significantly improved her headache. The diagnoses of pheochromocytoma subsequently lead to diagnosing her with medullary thyroid cancer (MTC) and multiple endocrine neoplasia type 2A (MEN-2A).